PENERAPAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN PNS BERDASARKAN PP NO 30 TAHUN 2015 - Widayanti, Wiwid; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
It has been found from the result of the research that the organization structure of the institution has metthe regulation standard of the Governorin which the tasks, authorities and responsibilities have been set but thecode of responsibility level has not been implemented yet. In accounting information the payroll of civilservanthas met the Standardof Government Regulation No. 30 of 2015 and the Standard of work guidelines andthe implementation of the tasks of the local government of East Java Province. In the Regional BudgetExpenditure has in accordance with the Standard of Regulation of Regional Budget Expenditure the salary ofcivil servant the 2016 fiscal year. The regional financial management has met the Regulation of Minister ofHome Affairs.The civil servant payroll report has been prepared based on the standard regulation of theGovernor of East Java and the accountability report of the realization of civil servant payroll has been preparedbased on the standard of Local Regulationssof the Supreme Consultative Council of Regional BudgetExpenditure.Keywords: system and procedures of civil servant payroll, regional budget, regional financial management